A aprendizagem significativa de sistemas de equações do 1º grau por meio da resolução de problemas - Goulart, Andreza Martins Antunes (2014)
This study aims to investigate whether the teaching and learning of equations of the 1st grade students from the 8th grade of elementary school systems, by means of solving problems allied to the principles of meaningful learning can contribute to an effective knowledge construction. This is a qualitative study, conducted by a teaching intervention has been proposed in which a sequence of activities, and data were collected through observation and classroom notes and analysis of students' protocols. The survey was conducted with students from the 8th grade of Elementary School from a private institution in the city of São Paulo, in which the researcher is a teacher. The content that was being developed at that time was the 1st degree equations systems with two unknowns, and the teaching methodology adopted by the teacher was focused on teaching mathematics through problem solving. The didactic proposal for this work was to introduce the contents of the system of equations by means of a sequence of activities, all developed in mathematics classrooms. From what was already known by the students, they solve the issues proposed in different situations, representing them by means of equations with two unknowns and adopting two different methods for the solution: the addition and replacement. The analysis of the protocols of students and notes taken during development activities indicates that students have noted that the proposals situations, the use of equations with two unknowns would require, unlike what happens in an equation of the 1st degree, and that when using the initial letters of words that correspond to the unknown, would facilitate this process. To be developed both methods of resolution, addition and substitution, students, despite some resistance presented by the second method, the end realized that, for different situations, one of the methods could facilitate the resolution of the proposed issue. After the completion and analysis of the instructional sequence , it can be concluded that teaching through problem solving contributes to greater understanding of what is being done and that this approach allows students to understand why the need to use the system equations of the 1st grade to solve certain situations . The use of each of the unknowns, thereby, as well as the importance of knowing two methods of resolution makes its meaningful learning